The Study of the Nutritive Condition of the Elderly Resident of Sari Sanatorium - Seyed Abdolhasan Naghibi; Arash Mohammadi; Abdolhamed Yusefi; Jamshid Yazdani Cherati (علوم بهداشتی ایران, 2014)
Abstract Background and purpose:The elderly resident of Sari sanatorium is vulnerable in terms of nutrition. This study has been conducted to investigate the nutritive condition of the elderly resident of Sari sanatorium in 2011. Materials and Methods:The method of the present study is periodic and descriptive type. The 104 elderly were studied. The samples’ anthropometric indices were measured, and mini nutritional assessment (MNA) questionnaire of the elderly was filled. At last, the total scores of nutritional state were calculated according to MNA and the relationship between the investigated factors and MNA scores were analyzed. Results:The result of the study showed that according to MNA, 38.62% of elderly under the investigation suffered from malnutrition and 40.38% were subject to malnutrition. In addition, the analysis of the data showed that there was a meaningful statistical relationship among the elderly nutritive states based on MNA, daily consumption of drug ability to move, neuropsychiatric problems, personal idea about their nutritive state, and health condition. Conclusion:There is an urgent need to include some nutritional interventions due to a high-degree of malnutrition and being subject to it in elderly sanatorium.